PEMILIHAN UMUM SEBAGAI TONGGAK DEMOKRASI DI INDONESIA - Robby Yunianto Utama MS (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Elections are a fundamental instrument for realizing popular sovereignty and represent a central pillar of democracy in Indonesia. As a mechanism that ensures the peaceful transfer of power, elections play a crucial role in strengthening governmental legitimacy, promoting accountability, and providing equal political participation opportunities for all citizens. However, the electoral process continues to face significant challenges, including widespread vote-buying, digital disinformation, low voter literacy, and weak law enforcement against electoral violations. These issues highlight the urgency of evaluating the effectiveness of elections as the foundation of Indonesian democracy. This study employs a normative legal research method using statutory, conceptual, and doctrinal approaches to examine the legal framework, principles, and practices governing elections. The results indicate that although Indonesia’s electoral regulations are relatively comprehensive, their implementation faces structural, technical, and cultural obstacles that undermine democratic quality. Strengthening electoral institutions, improving civic political education, and reforming the enforcement of electoral law are essential to ensuring that elections truly function as a cornerstone of democracy.Keywords: Election, Democracy, Law Enforcement